2022
DOI: 10.1097/01.gox.0000842340.30158.1e
|View full text |Cite
|
Sign up to set email alerts
|

3. Trends in Author Gender Among Diversity Studies in Plastic Surgery Literature

Abstract: Multiple Pearson's Chi-square of independence and Fisher's Exact tests evaluated comparisons of microaggressions by sex, race, Hispanic origin, sexual preference, and year in training. A multivariate regression analysis assessed associations between variables.Results: One hundred twenty-five participants responded to the survey (response rate: 10.2%). Of those who responded, 68.8% had experienced microaggressions in the past year. Female trainees experienced microaggressions more frequently than male trainees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Gunderson et al 66 evaluated the gender representation among breast, cosmetic, and hand/peripheral nerve articles published in Plastic and Reconstructive Surgery between 2006 and 2019, finding that the proportion of female corresponding authors increased in all 3 categories. In 2022, Bustos et al 75 reported that women represented 42.2% of total authors, 39.2% of first authors, and 36.5% of senior authors of publications discussing diversity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gunderson et al 66 evaluated the gender representation among breast, cosmetic, and hand/peripheral nerve articles published in Plastic and Reconstructive Surgery between 2006 and 2019, finding that the proportion of female corresponding authors increased in all 3 categories. In 2022, Bustos et al 75 reported that women represented 42.2% of total authors, 39.2% of first authors, and 36.5% of senior authors of publications discussing diversity.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 138 publications were identified 3–140 Figure 1. demonstrates the number of publications appearing annually in the 6 journals from January 2018 to September 2023.…”
Section: Resultsmentioning
confidence: 99%